Australia and the global trade system : - Capling, Ann (Cambridge University Press, 2001)
Australia and the World Trade System provides a comprehensive account of Australia's role in developing and maintaining the multilateral trade system from its origins in 1947 to the present day. This book, based on archival sources and oral interviews, makes a significant contribution to our understanding of Australia's trade policies, its commercial diplomacy, and its role and position in the global political economy.